The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17249501
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Women with Systemic Lupus Erythematosus: Association with Health-Related Parameters and Effects of Aerobic Exercise

Abstract: Abnormal heart rate variability (HRV) has been observed in patients with systemic lupus erythematosus (SLE). In a combined cross-sectional and interventional study approach, we investigated the association of HRV with inflammation and oxidative stress markers, patient-reported outcomes, and the effect of 12 weeks of aerobic exercise in HRV. Fifty-five women with SLE (mean age 43.5 ± 14.0 years) were assigned to either aerobic exercise (n = 26) or usual care (n = 29) in a non-randomized trial. HRV was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
2
1
Order By: Relevance
“…However, evidence data showed that systemic auto-immune disease as Sj€ ogren syndrome increase the levels of oxidative stress markers with severe repercussions on organs and organism (i.e. lipid metabolism, cardiovascular system, osteoarticular dysfunctions and exocrine functions) (Smallwood et al 2018;Charras et al 2019;Hu et al 2020;Mart ınez-Rosales et al 2020). Even if ageing decreases the antioxidative defences on ocular surface (Choy, Cho & Benzie 2011), we did not show any influence of age in oxidative stress homeostasis.…”
Section: Dry Eye Disease: a Disruption Of Ocular Surface Homeostasiscontrasting
confidence: 62%
See 1 more Smart Citation
“…However, evidence data showed that systemic auto-immune disease as Sj€ ogren syndrome increase the levels of oxidative stress markers with severe repercussions on organs and organism (i.e. lipid metabolism, cardiovascular system, osteoarticular dysfunctions and exocrine functions) (Smallwood et al 2018;Charras et al 2019;Hu et al 2020;Mart ınez-Rosales et al 2020). Even if ageing decreases the antioxidative defences on ocular surface (Choy, Cho & Benzie 2011), we did not show any influence of age in oxidative stress homeostasis.…”
Section: Dry Eye Disease: a Disruption Of Ocular Surface Homeostasiscontrasting
confidence: 62%
“…2020; Martínez‐Rosales et al. 2020). Even if ageing decreases the antioxidative defences on ocular surface (Choy, Cho & Benzie 2011), we did not show any influence of age in oxidative stress homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…They were asked to abstain from consuming alcohol and take a >6 h nap before the experiment. Additionally, caffeine consumption was restricted 3 h before the test [38], and the Ishihara test was administered to the participants for testing color blindness or color weakness [3]. Before the experiment, the subjects were directed to conduct a self-diagnosis of their health, and they were found to have a good health condition without any particular health problems.…”
Section: Participantsmentioning
confidence: 99%
“…Під її дією зменшується активність серцевосудинної системи, переважають процеси травлення та синтезу поживних речовин. У зв'язку з тим, що кожна тварина має індивідуальні особливості організму, вплив вищенаведених відділів може різнитися (Quevedo et al, 2019;Martínez-Rosales et al, 2020).…”
Section: вступunclassified
“…Для діагностики стану тварини часто використовували аналіз частоти серцевих скорочень під час доїння або дії больового фактору. З часом постало питання кращого аналізу серцевосудинної системи для дослідження впливу стресу на кіз (Kovács et al, 2019;Martínez-Rosales et al, 2020). Варіабельність серцевого ритму відображує активність автономної нервової системи в організмі.…”
Section: рис 3 варіаційна гістограма дослідної групи нормотоніківunclassified